MAGNETOOPTICAL STUDIES OF THE HEAVY-FERMION COMPOUND CENISN - Hill, S; Matsui, H; Hayes, W; Singleton, J; Blundell, S; Bucher, E; Hohl, H (1995)
Millimetre wave magneto-optical measurements have been performed for the first time on the valence fluctuating rare earth compound CeNiSn and a rich spectrum of sharp features is observed.